Pilgrim of America. Luz Vieira Méndez, Unesco’s first itinerant expert (1943-1971) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
This article stands out the career of Luz Vieira Méndez (1911-1971), a teacher, professor and magister who used one of the low possibilities to the female professionalization and its limited economical retribution, to go beyond the classroom. She was president of the National Council of Argentine Education, and the first woman who reached the highest leadership and management positions at the United Nations Educational, Scientific and Cultural Organization (UNESCO). Her intellectual production, like her activities of management and participation on institutional organizations are recovered in a biographical key with the intention to show, through her life, the most important contributions that women from the 60s and the 70s made to the argentine and Latin American educational field.
Keywords: teaching; education; women; education management; life stories